The development of the financial sector in Ireland, 1949-72 - Dowling, Brendan R. (Statistical and Social Inquiry Society of Ireland, 1974)
In the past decade or so there has been a considerable growth of interest in monetary economics. Part of this growth in interest can be attributed to the publication of important official enquiries in the US and the UK - the Commission on Money and Credit and the Radcliffe Report. Another important factor was, perhaps, an inevitable swing back from the excesses of the post-Keynsians who relegated money to a very minor role in the macro-economic process. In recent years also the problems of monetary policy in open economies have been the attention of considerable research and, in a world of internationally mobile capital, balance of payments positions are examined from a monetary, rather than a purely tradeoriented, standpoint.
Read before the Society, 28 March 1974
Keywords: Irish financial sector; Money supply; Portfolio structure; Government involvement in financial sector; Monetary policy; 314.15